Analisis Keputusan Pembelian Mie Samyang Halal Di Jakarta - Maharani, Novida; Handayani, Tati; Priyatno, Prima Dwi (DPPM Universitas Pelita Bangsa, 2021)
This study aims to analyze and prove the effect of halal labels and promotions on purchasing decisions for samyang noodles in Jakarta. The population used in this study is the people of Jakarta. The sampling used was using the Lemeshow formula by determining the unknown population size of 100 respondents. Data analysis techniques to determine the magnitude of the effect of halal labels and promotions on purchasing decisions for samyang noodles are Validity Test, Reliability Test, Classical Assumption Test, and Multiple Linear Regression, t-test, f-test, and Coefficient of Determination Test with the help of SPSS 20. The results of this study shows that the halal label has a significant positive effect on purchasing decisions for samyang noodles, and promotions has a significant positive effect on purchasing decisions for samyang noodles. Halal label and promotion together have a significant influence on purchasing decisions for samyang noodles. Research that has been carried out and carried out still has many shortcomings and limitations in its manufacture so that the limitations that limit this research are the